Massachusetts' Findings from Statewide Newborn Screening for Spinal Muscular Atrophy - Jaime E. Hale; Basil T. Darras; Kathryn J. Swoboda; Elicia Estrella; Jin Yun Helen Chen; Mary-Alice Abbott; Beverly N. Hay; Binod Kumar; Anne M. Counihan; Jacalyn Gerstel-Thompson; Inderneel Sahai; Roger B. Eaton; et al. (MDPI AG, 2021)
Massachusetts began newborn screening (NBS) for Spinal Muscular Atrophy (SMA) following the availability of new treatment options. The New England Newborn Screening Program developed, validated, and implemented a screening algorithm for the detection of SMA-affected infants who show absent SMN1 Exon 7 by Real-Time™ quantitative PCR (qPCR). We screened 179,467 neonates and identified 9 SMA-affected infants, all of whom were referred to a specialist by day of life 6 (average and median 4 days of life). Another ten SMN1 hybrids were observed but never referred. The nine referred infants who were confirmed to have SMA were entered into treatment protocols. Early data show that some SMA-affected children have remained asymptomatic and are meeting developmental milestones and some have mild to moderate delays. The Massachusetts experience demonstrates that SMA NBS is feasible, can be implemented on a population basis, and helps engage infants for early treatment to maximize benefit.